Mechanical and electrical properties of the Bi-Ge-Sn alloys - Djordjevic, Aleksandar; Premovic, Milena; Minic, Dusko; Tomovic, Milica; Radicevic, Branko; Kolarevic, Nemanja (Metallurgical and Materials Engineering, 2020)
Mechanical and electrical properties of the ternary Bi-Ge-Sn alloys were investigated in this study. Calculation of isothermal section at 200, 300, and 25 ºC was carried out by using optimized thermodynamic parameters for the constitutive binary systems. Microstructures of alloys were observed by using optical microscopy and scanning electron microscopy (SEM). Phases in microstructures have been detected by X-ray diffraction (XRD) analysis and compositions of the phase by energy dispersive spectrometry (EDS). EDS results were compared with the predicted isothermal section at 200 and 300 ºC, and good agreement has been reached between them. The Brinell hardness and electrical conductivity of selected alloys were measured. Through ANOVA analysis and application of the obtained results, an appropriate mathematical model is proposed for every composition of alloys. By using the appropriated mathematical model for Brinell hardness and electrical conductivity, isolines for those properties were presented.